Holistic self-management behavior among urban patients with type 2 diabetes - An Ha Thi Tran; Ngoc Nguyen Tran (International Journal of Public Health Science (IJPHS), 2022)
This study aimed to measure the self-care practices of type 2 diabetes mellitus (T2DM) patients managed in an urban hospital in Hanoi, Vietnam. An observational cross-sectional study was performed. The adherence of self-care practices was measured by using the Condition-specific Recommendations and Adherence scale. Among 165 T2DM patients, nobody adhered to all self-care practices. The average number of adhered behavioral recommendations was 6.0 (SD=1.6). Gender, education and overweight/obesity were associated with self-care practice adherence. Repeated educational sessions should be provided to patients, especially male patients, and those with low education levels, overweight/obese, to improve their self-care ability.